Thung Makham Yong: History and the Monument of Suriyothai - Nanrum, Supakan; Ketsomboon, Natthaya (Mahachula Academic Journal, 2025)
This study aims (1) to examine the historical context of relations between Thailand and Burma during 1534–1548 CE, (2) to investigate Thung Makham Yong within the broader framework of Thai history and (3) to study the relationship between the Monument of Queen Suriyothai and the people of Phra Nakhon Si Ayutthaya. This documentary research collects both primary and secondary historical sources and conducts content analysis to explore the spatial historical development of the area in relation to tourism. The findings reveal that: (1) Following the death of King Borommarachathirat IV, the political stability of the Ayutthaya Kingdom weakeness, seized the vassal cities of Ayutthaya] the Mon cities war occurred between the two kingdoms. (2) The Burmese invasion of 1548 CE, known as the war during which Queen Suriyothai was slain on elephant-back, is widely recorded in the Royal Chronicles of Ayutthaya, which highlight her bravery and identify Thung Makham Yong as the battlefield. The area also served as a northern floodplain for the Ayutthaya island-city. (3) With the intention of Her Majesty Queen Sirikit The Queen Mother to honor and disseminate the legacy of Queen Suriyothai, the Monument of Queen Suriyothai was constructed at Thung Makham Yong in 1992. The monument holds significance as an important historical site, a water-retention area, a source of agricultural water, and a historical tourist attraction for the people of Phra Nakhon Si Ayutthaya Province.